Access to Phylogeny from Voltammetric Fingerprints of Seeds: the Asparagus Case. Issue 2 (15th November 2016) - Doménech‐Carbó, Antonio; Ibars, Ana M.; Prieto‐Mossi, Josefa; Estrelles, Elena; Doménech‐Carbó, María Teresa; Ortiz‐Miranda, Annette S.; Martini, Mariele; Lee, Yu
Abstract: A methodology for characterizing vegetal taxonomic groups from the voltammetric fingerprints of polyphenolic components of seeds is described. It is based on recording the voltammetric response of microparticulate films deposited on glassy carbon electrodes from seed extracts using different organic solvents. The obtained responses in contact with aqueous electrolytes provided characteristic voltammetric profiles at the level of genera/subgenera and/or families using bivariant and multivariant chemometric methods. The voltammograms of 14 species from 5 different families provided family‐characteristic patterns. Analysis of voltammetric responses for a set of 20 species of the Asparagus genus from four continents permits to discriminate the genetic lines represented by the Asparagus, Protasparagus and Myrsiphyllum subgenera. Abstract :